Kinesins in Mammalian Spermatogenesis and Germ Cell Transport - Yao, Mingxia; Qu, Haoyang; Han, Yating; Cheng, C. Yan; Xiao, Xiang (Frontiers in Cell and Developmental Biology, 2022)
In mammalian testes, the apical cytoplasm of each Sertoli cell holds up to several dozens of germ cells, especially spermatids that are transported up and down the seminiferous epithelium. The blood-testis barrier (BTB) established by neighboring Sertoli cells in the basal compartment restructures on a regular basis to allow preleptotene/leptotene spermatocytes to pass through. The timely transfer of germ cells and other cellular organelles such as residual bodies, phagosomes, and lysosomes across the epithelium to facilitate spermatogenesis is important and requires the microtubule-based cytoskeleton in Sertoli cells. Kinesins, a superfamily of the microtubule-dependent motor proteins, are abundantly and preferentially expressed in the testis, but their functions are poorly understood. This review summarizes recent findings on kinesins in mammalian spermatogenesis, highlighting their potential role in germ cell traversing through the BTB and the remodeling of Sertoli cell-spermatid junctions to advance spermatid transport. The possibility of kinesins acting as a mediator and/or synchronizer for cell cycle progression, germ cell transit, and junctional rearrangement and turnover is also discussed. We mostly cover findings in rodents, but we also make special remarks regarding humans. We anticipate that this information will provide a framework for future research in the field.